2021
DOI: 10.3390/beverages7030060
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dadih: Traditional Fermented Buffalo Milk of Minangkabau

Abstract: Dadih or dadiah is traditional fermented buffalo milk of Minangkabau, which occurs spontaneously. Dadih is commonly served as ampiang dadih, or other dishes. The microbiota found in dadih are dominated by lactic acid bacteria, and yeasts are also found. The lactic acid bacteria provide functional value, such as antimicrobial, hypocholesterolemic, antimutagenic, antioxidant, and immunomodulatory properties, as well as being the source of γ-aminobutyric acid (GABA) as an anti-stress agent and folate. Nevertheles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…At the cozy temperature, thermophilic bacteria are usually isolated from dadiah, which depends on room temperature for incubation spontaneous fermentation. No wonder previous researchers keep isolating thermophilic bacteria as Lactic acid bacteria in dadiah [7], [8], [3], and [1].…”
Section: Location Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cozy temperature, thermophilic bacteria are usually isolated from dadiah, which depends on room temperature for incubation spontaneous fermentation. No wonder previous researchers keep isolating thermophilic bacteria as Lactic acid bacteria in dadiah [7], [8], [3], and [1].…”
Section: Location Researchmentioning
confidence: 99%
“…The menu described above is known as Ampiang Dadiah. Ampiang in minangese describes as FGR [3]. In the process, FGR were flattened-pre-roasted rice [4].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of bacteria found in dadih can make use of the change in pH value. According to [17] the lactic acid generated can cause buffalo milk to coagulate into dadih and have a negative impact on the pH level of the milk by causing protein deposition. The type of bamboo used can also impact the pH level of the dadih because bamboo can also create organic acid subtances such oxalic acid, citric acid, malic acid and succinic acid.…”
Section: Ph Valuementioning
confidence: 99%
“…[13] reported that the pH of traditionally fermented goat milk whey in ori bamboo tubes had a pH value of 6.47. Whereas in research [14] that cow's milk whey with a combination of starters has a pH range between 3.99 to 4.07.…”
Section: Degree Of Acidity (Ph) Of Buffalo Wheymentioning
confidence: 99%